Efektivitas Penyebaran Informasi di Bidang Pertanian melalui Perpustakaan Digital (Kasus Pusat Perpustakaan dan Penyebaran Teknologi Pertanian) - S. Maryam; M. Hubeis; Maksum . (Jurnal Komunikasi Pembangunan, 2009)
The research was conducted to know and analyze the effectiveness of agricultural information dissemination throughdigital library. The characteristic, information accessibility and communication intensity of library user and thecorrelation of their variables was analyzed partially or simultaneously. The research location was performed atPusat Perpustakaan dan Penyebaran Teknologi Pertanian (PUSTAKA) Bogor, and conducted from March until June2008. This research was designed by using a survey method with correlation descriptive. Data collected byquestionnaire and the samples were taken by employing a non-probability sampling method with conveniencesampling, involving 82 respondents which consists the library user of university student. The analysis was done bydescriptive frequency and inferential analysis with Rank Spearman correlation by SPSS 16.0 for windows program.The result showed that the characteristic, information accessibility and communication intensity of library user bytogether didn’t show significantly correlation with the diffusion effectiveness of agricultural through digital library atPUSTAKA Bogor. It means the user come to the library to look for the information what they need, it doesn’t showcorrelation with the availability of facilities at PUSTAKA. However the correlation occurring between thecharacteristic of library user and information accessibilities was shown significantly. The diffusion of agriculturalthrough digital library at PUSTAKA Bogor has already run effectively. Therefore, it can be as a reference for thesame library to other libraries in Indonesia for developing the digital library. The digital library of PUSTAKA shouldpromote to the public with publicity and advertisement, especially through television as the digital library beingcomplete and modern in agriculture sector.